Logistics System Just-In-Time and its Implementation within the Company - Kubasakova, Iveta; Jagelcak, Juraj (Communications - Scientific Letters of the University of Zilina, 2016)
Just-In-Time (JIT) is a logistics system with its own technology for supply, production, distribution and management within the company. This article describes the technology of how to apply the JIT system in the company, about legal aspects of JIT and its positive and negative impact on the company's profits.
Keywords: logistics system; implementation; legal aspect; positive; negative